Three-dimensional morphological study of type B lateral malleolar fractures with special reference to the end-tip location of proximal apexes - Wang, Wei-Bin; Chang, Shi-Min (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: We aimed to describe the morphological characteristics of Danis–Weber type B lateral malleolar fractures, with special attention given to the end-tip locations of fracture apexes, and to construct a 3D (three-dimensional) fracture line map. Methods: A total of 114 surgically treated cases of type B lateral malleolar fractures were retrospectively reviewed. The baseline data were collected, and computed tomography data were reconstructed in a 3D model. We measured the morphological characteristics and the end-tip location of the fracture apex on the 3D model. All the fracture lines were superimposed on a template fibula to generate a 3D fracture line map. Results: Among these 114 cases, 21 were isolated lateral malleolar fractures, 29 were bimalleolar fractures, and 64 were trimalleolar fractures. All the type B lateral malleolar fractures demonstrated a spiral or oblique fracture line. As measured from the distal tibial articular line, the fracture started at −6.22 ± 4.62 mm anteriorly and terminated at 27.23 ± 12.32 mm posteriorly, and the average fracture height was 33.45 ± 11.89 mm. The fracture line inclination angle was 56.85° ± 9.58°, and the total fracture spiral angle was 269.81° ± 37.09°, with fracture spikes of 156.20° ± 24.04°. The proximal end-tip location of the fracture apex was classified into four zones in the circumferential cortex: zone I (lateral ridge) in seven cases (6.1%), zone II (posterolateral surface) in 65 cases (57%), zone III (posterior ridge) in 39 cases (34.2%), and zone IV (medial surface) in three cases (2.6%). Altogether, 43% (49 cases) of fracture apexes were not distributed on the posterolateral surface of the fibula, as 34.2% (39 cases) were located on the posterior ridge (zone III). The aforementioned morphological parameters in fractures with zone III, sharp spikes, and further broken spikes were greater than those in zone II, blunt spikes, and fractures without further broken spikes. The 3D fracture map suggested that the fracture lines with the zone-III apex were steeper and longer than those with the zone-II apex. Conclusion: Nearly half of type B lateral malleolar fractures had their proximal end-tip of apexes not on the posterolateral surface, which may impair the mechanical application of antiglide plates. A steeper fracture line and longer fracture spike indicate a more posteromedial distribution of the fracture end-tip apex.